Case Report: Development of medication-related osteonecrosis of the jaw in a patient on long-term infliximab therapy - Oryniak, Derek; Brown, Meagan; Cholakis, Lillie; Elgazzar, Reda (Frontiers in Oral Health, 2024)
Medication-Related Osteonecrosis of the Jaw (MRONJ) is a challenging and evolving aspect of Oral and Maxillofacial Surgery. In recent years, several medications apart from those traditionally associated with MRONJ such as bisphosphates (BPs) and Denosumab (DMB) have been implicated in bony necrosis of the jaw. This aim of this report is to demonstrate a significant case of bone necrosis following dental extractions on a patient being treated with infliximab therapy for Crohn's disease. Several cases in literature have reported MRONJ associated with infliximab but very few patients have developed as significant a form of the disease as seen in this report. Previous investigators have proposed pathophysiological pathways via which TNF-α inhibitors such as infliximab have a causative mechanism for MRONJ. When osteoclastic activity is restricted via these pathways, bone healing is impaired and MRONJ can occur. However, it remains a diagnostic challenge to differentiate between antiresorptive MRONJ and chronic osteomyelitis with bone necrosis in patients with acquired immunodeficiency. This case aims to illustrate why the antiresorptive effects of TNF-α inhibitors need to be considered as a possible primary driver of bone necrosis in such patients.